Metafora dalam Bidang Pertanian Padi Masyarakat Dayak Buket Kabupaten Kutai Barat Kalimantan Timur (Suatu Tinjauan Linguistik Antropologi) - Ishak Bagea (Humaniora, 2010)
Metaphor in the field of rice farming is not only an unusual form of utterances in a society but also an indication of the local wisdoms of the society using them. This can be seen in the Dayak Buket society in Linga Tivab village, Long Apari district, West Kutai, East Kalimantan, which has strong Dayak cultural background. This research aims at describing the forms and the types of metaphor based on its elements as well as describing the worldviews of Dayak Buket society as reflected through the use of metaphor that they ised in the field of rice farming. This research employs descriptive qualitative method which covers three steps, namely, data collection, data analysis, and result presentation of data analysis. The data collection is executed by recording the utterances, transcribing the utterances phonetically, classifying the according to the kinds of semantic field of metaphor in the field of rice farming, analyzing the forms of metaphor and the description of its types based on the underlying elements, and describing the local wisdoms that exist in the metaphor. This research results in both the exposition of the forms of metaphor of the Dayak Buket society such as verbs, nouns, adjectives, verbal phrases, noun phrases, adjective phrases, and their worldviews which can be recognized from the metaphors that hey use in the field of rice farming.